The potential encapsulation of euphorbiaceae plant extracts: a review - Johari, Maizatul Akmal; Ali, Fathilah; Azmi, Azlin Suhaida; Jamaluddin, Jamarosliza; Hasham, Rosnani (Universiti Kebangsaan Malaysia Press, 2021)
Encapsulation is a way to stabilize the bioactive compounds from the plant extracts. Previously, encapsulation techniques have been widely studied in modern drugs. For instance, the hydrophobic drugs such as celecoxib, diosmin, exendin-4, 5-fluorouracil and paclitaxel; and hydrophilic drugs such as amoxicillin and insulin. Euphorbiaceae is a family of kingdom Plantae rich in pharmaceutical constituents that have been proved in traditional medicines but getting less attention in terms of encapsulation studies. Euphorbiaceae has a big potential for the application of drug delivery in pharmaceutical industry by improving their stability using microencapsulation or nanoencapsulation. Similar models in the encapsulation of modern drugs can be used in the encapsulation of plant bioactive compounds according to their hydrophilicity or hydrophobicity. This paper also suggested some plant species in Euphorbiaceae that has never been reported on the encapsulation for next exploration.